Exploring the process of adjustment to a diagnosis of dementia at working-age: a qualitative study - Williams, Francesca (2019)
42,000 people are thought to be living with a diagnosis of working-age dementia (WAD) in the UK (Prince, 2014). For the person with dementia, the unexpectedness of receiving a diagnosis at this age (Roach, Drummond, & Keady, 2016), alongside other factors, may lead to additional difficulties to those diagnosed at an older-age. In addition, informal carers are thought to suffer significantly greater levels of stress than their older-age counterparts (Luscombe, Brodaty, & Freeth, 1998).